Contribution of primary health care teams to equity in universal access to health services - Gustavo Bergonzoli; Lina María García Zapata (Archives of Preventive Medicine - Peertechz Publications, 2019)
Since Alma Ata Declaration, 40 years ago, the Health Service Systems has undergone signifi cant changes, but those achievements are unevenly distributed, with an increasing number of people without coverage by basic health services. Advances in technology, including the arrival of big data, together with the adoption of evidence-based care models have been transformative, especially for primary health care [1]. The strengthening of Primary Health Care (PHC) has been proposed as the best instrument to achieve more effi cient and equitable health systems. When comparing several countries with the same degree of economic development, for the same investment, those who have organized health care around the postulates of primary health care enjoy a higher level of health [2].